Between Dominance and Subservience: A Comparative Study of Executive Power in Ireland, the United Kingdom, and the United States. - Casey, Conor (Trinity College Dublin. School of Law. Discipline of Law, 2021)
This thesis undertakes a comparative constitutional analysis of the position of the political executive in Ireland, United Kingdom, and the United States. I address three central questions. First, why has the executive become the most powerful and predominant branch of each state? Second, what does its predominant status tell us about the conceptual nature of the political executive in these, and similar, constitutional systems? Third, is the predominant status of the political executive a normatively positive or negative feature of these political systems? These questions are important by virtue of the fact the political executive is the centre of public power in the contemporary state, despite the fact historical and formal legal accounts of executive power are modest - a pale reflection of the executive?s current predominant status. Methodologically, my study takes the form of a comparison of three qualitative case-studies. I build my arguments based on inductive observations taken from a small sample of contextual and detailed case studies. A small number of highly detailed cases studies allows for a more rigorous qualitative analysis of how constitutional power is actually allocated and exercised in practice. This, in turn, allows for the building of robust narratives providing a solid explanatory foundation for both the why of executive predominance and the executive?s conceptual nature. I argue the root of executive predominance lies in each political system?s attempt to increase the ability of the state to use public power to meet the political expectations, fears, and hopes of the polity, and to promote the common good. Pressures placed on the state to meet complex social and political challenges has pressed each system to evolve its constitutional order. This evolution came in the form of a diffusion of power to the executive, based on its superior institutional capacity to use it, far outstripping other political actors. It was the executive that was bestowed, above any other branch, the daunting role of steering the polity through the complexities and dangers of contemporary government. After tracing the common forces and trends which underpin the status of the executive, I offer a conceptual account of the nature of the executive branch in each system. I argue historical conceptions of the executive as faithful executioner of the law created by representative assemblies offer an unsatisfactory account of the contemporary executive, as do accounts of the executive as kind of elected dictatorship unbound by law. Instead, I make the case each system has a political executive with a similar - and pronounced - conceptual tension between legal subservience on the one hand and political dominance on the other. By tying these dualities together, I offer a more analytically and descriptively accurate and helpful understanding of its conceptual nature. I suggest each system can be conceptually understood as having a ?Constrained Primacy Model of Executive Power?, one where the executive is highly predominant in the formation and execution of domestic and foreign policy; vested with very capacious administrative, regulatory, and security powers; but genuinely constrained within the bounds of legality. Finally, I conclude with a qualified defence of the constrained primacy model of executive power. I argue adequately responding to the challenges of contemporary government can require embrace of strong executive authority, and that an enfeebled executive can leave the polity less able to use public power to secure conditions like domestic order and social justice ? and a host of other goals which are closely linked to the common good. But my defence is qualified in the sense I argue a predominant executive must be accompanied by a constitutional and political culture broadly dedicated to aiming its capacity toward the common good. This is because a powerful executive is inevitably a double-edged sword. It is potentially a more efficient tool for evil purposes, as it faces less veto-points in having its bad preferences changed into public policy. As such, a combination of such a potent institution with the erosion of a political culture orientated toward the common good could easily produce toxic effects. Offering a via media between these concerns, I conclude it is normatively defensible to argue that, in political systems where the right conditions hold, it is not the mere existence of a powerful executive that should be our primary concern, but who wields this authority, where its power is directed, and why.
APPROVED
Keywords: Executive power, constitutional theory, comparative constitutional law.